Assessment of flood recession agriculture for food security in northern Ghana: an optimization modelling approach - Balana, Bedru; Sanfo, S.; Barbier, B.; Williams, Timothy; Kolavalli, S. (Elsevier, 2019)
Food insecurity is a recurrent problem in northern Ghana. Food grown during the rainy season is often insufficient to meet household food needs, with some households experiencing severe food insecurity for up to five months in a year. Flood recession agriculture (FRA) – an agricultural practice that relies on residual soil moisture and nutrients left by receding flood water – is ordinarily practiced by farmers along the floodplains of the White Volta River in northern Ghana under low-input low-output conditions. Opportunities abound to promote highly productive FRA as a means of extending the growing season beyond the short rainy season (from May to September) into the dry season and thereby increase household income and food security of smallholder farmers. This study uses an optimization modelling approach to explore this potential by analyzing the crop mix and agricultural water management options that will maximize household income and enhance food security. Results indicate that growing cowpea, groundnut and melon under residual-moisture based FRA and high value crops (onion, pepper, and tomato) under supplementary irrigation FRA maximize household income and food security. The cash income from the sale of FRA crops was sufficient to purchase food items that ensure consumption smoothing during the food-insecure months. The study concludes that the full potential of FRA will be realized through a careful selection of crop mixtures and by enhancing access of farmers to improved seeds, integrated pest management and credit and mainstreaming FRA through targeted policy interventions and institutional support.